2011
DOI: 10.4161/jig.19958
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of contrast harmonic endosonography using DEFINITY™ in the evaluation of suspected pancreatic and peri-ampullary malignancies

Abstract: Aim: contrast harmonic endosonography (cheUs) is not widely available. This study assessed the utility of cheUs using DeFINITY™, a second generation ultrasonic contrast agent, in the evaluation of suspected pancreatic and peri-ampullary malignancies. Methods: prospectively enrolled patients with suspected pancreatic and peri-ampullary malignancies underwent eUs followed by cheUs. The incremental yield of cheUs over eUs was analyzed. The gold standard for diagnosis of malignancy was positive cytology or histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nucleotides 2–8 at the 5′ end of a mature miRNA are referred to as the ‘seed sequences’ essential for miRNA‐mediated gene silencing . Recent studies also revealed the important role of miRNAs in modulating the expression of various cytokines and chemokines , which participate in inflammation infiltration and complication of multiple diseases, including pancreatic fibrosis and CP . Interestingly, aberrant miRNA expression can also be used as indicator for disease progression, which consequently offers a potential tool for diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotides 2–8 at the 5′ end of a mature miRNA are referred to as the ‘seed sequences’ essential for miRNA‐mediated gene silencing . Recent studies also revealed the important role of miRNAs in modulating the expression of various cytokines and chemokines , which participate in inflammation infiltration and complication of multiple diseases, including pancreatic fibrosis and CP . Interestingly, aberrant miRNA expression can also be used as indicator for disease progression, which consequently offers a potential tool for diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…Published data (retrospective and prospective studies, randomly allocated control trials, meta-analysis) have consistently confirmed the validity and usefulness of CH-EUS in this respect. The literature search revealed 3 systematic reviews or meta-analyses (D'Onofrio et al 2014;Fusaroli et al 2016c;Yamashita et al 2019), 36 studies that focused on characterization of solid masses using contrast EUS alone (Hirooka et al 1998;Becker et al 2001;Hocke et al 2006Hocke et al , 2007Sakamoto et al 2008;Dietrich et al 2005Dietrich et al , 2008Napoleon et al 2010;Kitano et al 2008aKitano et al , 2012S aftoiu et al 2010;Fusaroli et al 2010;Seicean et al 2010;Ang et al 2011;Matsubara et al 2011;Imazu et al 2012;Gheonea et al 2013;Lee et al 2013;Gincul et al 2014;Park et al 2014;Uekitani et al 2016;Omoto et al 2017;Cho et al 2018;Leem et al 2018;Ishikawa et al 2018), and 4 studies that combined both CH-EUS and EUS elastography to characterize pancreatic solid masses (Figueiredo et al 2012;Hocke et al, 2012;S aftoiu et al 2015;Chantarojanasiri et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Published studies have shown CHEUS to be useful in the detection and differentiation of pancreatic lesions, and in the assessment of T staging. [60][61][62][63][64][65] A recently published metaanalysis reported that the pooled sensitivity of CHEUS for the differential diagnosis of pancreatic adenocarcinomas was 94% (95% confidence interval [CI], 0.91-0.95), and the specificity was 89% (95% CI, 0.85-0.92). 60 EUS elastography.…”
Section: Imaging Technologiesmentioning
confidence: 99%